2022
DOI: 10.2460/ajvr.22.07.0118
|View full text |Cite
|
Sign up to set email alerts
|

The titers, duration, and residual clinical protection of passively transferred nasal and serum antibodies are similar among beef calves that nursed colostrum from vaccinated or unvaccinated dams and were challenged experimentally with bovine respiratory syncytial virus at three months of age

Abstract: OBJECTIVES To compare initial titers, duration, and residual clinical protection of passively transferred bovine respiratory syncytial virus (BRSV) nasal immunoglobulin (Ig) G-1 and IgA, and serum neutralizing (SN) antibodies. ANIMALS 40 three-month-old beef steers born either to unvaccinated or vaccinated cows. PROCEDURES During the last trimester of gestation, cows were assigned randomly to either vaccinated or unvaccinated groups. Calves were grouped on the basis of whether they nursed colostrum from un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is possible that high levels of BRSV IgG-1 transferred from maternal colostrum to the upper respiratory tract prevented priming and induction of detectable levels of BRSV IgA in Vacc calves following vaccination at birth. Results from a previous study demonstrated high levels of colostrum-derived nasal BRSV IgG-1 in calves that nursed colostrum from dams vaccinated with an inactivated-BRSV vaccine before calving [ 9 ]; however, nasal BRSV IgG-1 completely decayed before 1-month of age. This is consistent with the initial nasal BRSV IgG-1 titers and decay detected in Vacc and Control calves from this study and reflects the adequate transfer of passive immunity as demonstrated by serum Brix values [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that high levels of BRSV IgG-1 transferred from maternal colostrum to the upper respiratory tract prevented priming and induction of detectable levels of BRSV IgA in Vacc calves following vaccination at birth. Results from a previous study demonstrated high levels of colostrum-derived nasal BRSV IgG-1 in calves that nursed colostrum from dams vaccinated with an inactivated-BRSV vaccine before calving [ 9 ]; however, nasal BRSV IgG-1 completely decayed before 1-month of age. This is consistent with the initial nasal BRSV IgG-1 titers and decay detected in Vacc and Control calves from this study and reflects the adequate transfer of passive immunity as demonstrated by serum Brix values [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transfer of colostral BRSV-specific immunoglobulin G-1 (IgG-1) into the upper respiratory tract of young calves not only could protect against infection but also block BRSV vaccine antigens from IN vaccination. Results from a previous study demonstrated considerable levels of nasal BRSV-IgG-1 at 48 h of life of beef calves that nursed colostrum from their dams [ 9 ]. Additionally, results from previous studies suggest that the duration of local antibody responses (i.e., BRSV-specific immunoglobulin-A) induced by vaccination of calves with IN MLV BRSV vaccines between 3 and 11 days of age is short-lived [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%